(untitled) (Research, Society and Development, 2020)
The study aims to identify the different types of violence against women, with an emphasis on the contextualization of emotional abuse by their intimate partners. This is a descriptive, qualitative integrative literature review, of a qualitative nature, carried out by searching for articles indexed in the Virtual Health Library (VHL), with the help of the following databases: Scientific Electronic Library Online (SCIELO), National Center for Biotechnology Information (PUBMED), Latin American and Caribbean Literature in Health Sciences (LILACS), Nursing Database (BDENF), and Electronic Journals in Psychology (PEPSIC). The inclusion criteria include literature review research available in the databases described, between the years 2000 to 2020. The exclusion criteria were duplicate, incomplete articles, abstracts, reviews, debates, experience reports, articles published in annals of events and unavailable in full. For data collection, 19 articles and 05 studies referring to health entities were analyzed. The results of the study show that the lack of information regarding the types of violence is still very visible among women victims of some type of violence. Thus, we can conclude that the aggressor will not always physically attack, leaving visible marks on the victims’ bodies. Moral, psychological, patrimonial violence, needs greater visibility, so that women expand their knowledge about the situation that is inserted, in order to identify the situation of violence, and to deal with the problems developed in an assistential and humanized way.